2018
DOI: 10.1016/j.jacc.2018.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Unloading Before Reperfusion Promotes Functional Recovery After Acute Myocardial Infarction

Abstract: The authors report for the first time that first mechanically reducing LV work before coronary reperfusion with a transvalvular pump is necessary and sufficient to reduce infarct size and to activate a cardioprotective program that includes enhanced SDF-1α activity. Primary unloading further improved LV scar size and cardiac function 28 days after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
106
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 31 publications
0
106
0
2
Order By: Relevance
“…It consists of a miniaturised axial flow pump fitted onto a pigtail catheter, pumping blood from the left ventricle into the ascending aorta and providing a cardiac output of 2.5 L/min (Impella 2.5) and up to 4.0 L/min (Impella CP) 5 6. It actively unloads the left ventricle reducing the stroke-work and myocardial oxygen consumption, thereby providing cardioprotection and robust haemodynamic support 7–9…”
Section: Introductionmentioning
confidence: 99%
“…It consists of a miniaturised axial flow pump fitted onto a pigtail catheter, pumping blood from the left ventricle into the ascending aorta and providing a cardiac output of 2.5 L/min (Impella 2.5) and up to 4.0 L/min (Impella CP) 5 6. It actively unloads the left ventricle reducing the stroke-work and myocardial oxygen consumption, thereby providing cardioprotection and robust haemodynamic support 7–9…”
Section: Introductionmentioning
confidence: 99%
“…Recent extensive animal studies showed that mechanical unloading of the left ventricle before coronary reperfusion limits the expression of proteolytic enzymes. This resulted in less cell decay, reduced infarction size and better haemodynamic performance [33]. A recent clinical trial also showed promising results when the Impella support was initiated before emergency PCI [34].…”
Section: Discussionmentioning
confidence: 99%
“…28 The mechanisms underlying this cardioprotective effect of primary unloading, and its impact of LV scar size were further explored by a seminal preclinical study by the same group. 22 In this study, male Yorkshire swine was subjected to either 90 minutes of mid-LAD occlusion followed by immediate reperfusion (primary reperfusion group) or 30 minutes of unloading before reperfusion (primary unloading group). Primary unloading increased the expression of genes associated with cellular respiration and mitochondrial integrity within the infarct zone, reduced activity levels of proteases known to degrade the cardioprotective cytokine, stromal-derived factor (SDF)-1a, limiting apoptosis in the infarct zone (Figure 1).…”
Section: Unloading-pre Clinical Datamentioning
confidence: 99%